Two phase transitions in (s+id)-wave Bardeen-Cooper-Schrieffer superconductivity - Ghosh, A.; Adhikari, S. K. (Iop Publishing Ltd, 1998)
We establish universal behaviour in the temperature dependencies of some observables in (s + id)-wave BCS superconductivity in the presence of a weak a wave. We find also a second second-order phase transition. As temperature is lowered-past the usual critical temperature T-c, a less ordered superconducting phase is created in the d wave, which changes to a more ordered phase in a (s + id) wave at T-c1 (<T-c). The presence of two phase transitions is manifested by the two jumps in the specific heat at T-c and T(c)1. The temperature dependencies of the susceptibility, penetration depth, and thermal conductivity also confirm the existence of the new phase transition.